2019
DOI: 10.1108/cms-04-2018-0495
|View full text |Cite
|
Sign up to set email alerts
|

The influence of abusive supervision on employees’ motivation and extra-role behaviors

Abstract: Purpose The purpose of this paper is to attempt to unlock how and why abusive supervision influences employees’ day-to-day behaviors. Thus, the present study proposes that employees who are continuously faced with a supervisor’s hostile verbal and nonverbal behavior might obstruct their willingness to exhibit two different kinds of extra-role behaviors [i.e. organizational citizenship behavior (OCB) and voice] because sustained abusive behavior might hinder employees from their tasks and result in disengagemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 42 publications
1
38
0
Order By: Relevance
“…This finding provides an interesting complement to JD-R studies that find stronger relationships of job resources, rather than job demands, with work engagement (Bakker et al, 2014;Halbesleben, 2010). Our theoretical framework does not include job resources -so a direct comparison of their effects on work engagement, relative to those of job demands, is not feasible -but the prominent mediating role of work engagement that we identify is consistent with prior research on the detrimental effect of hindrance demands on work engagement (Barnes et al, 2015;Huang et al, 2019). As Barnes et al, (2015Barnes et al, ( : 1423) explicate, 'subordinate motivation is proximal psychologically to abusive behaviour and thus likely to be a strong psychological outcome for subordinates experiencing abusive supervision', so 'by providing an experience that employees will find aversive, abusive supervision should leave employees more likely to withdraw than to engage themselves heavily in their work'.…”
Section: Theoretical Implicationssupporting
confidence: 67%
“…This finding provides an interesting complement to JD-R studies that find stronger relationships of job resources, rather than job demands, with work engagement (Bakker et al, 2014;Halbesleben, 2010). Our theoretical framework does not include job resources -so a direct comparison of their effects on work engagement, relative to those of job demands, is not feasible -but the prominent mediating role of work engagement that we identify is consistent with prior research on the detrimental effect of hindrance demands on work engagement (Barnes et al, 2015;Huang et al, 2019). As Barnes et al, (2015Barnes et al, ( : 1423) explicate, 'subordinate motivation is proximal psychologically to abusive behaviour and thus likely to be a strong psychological outcome for subordinates experiencing abusive supervision', so 'by providing an experience that employees will find aversive, abusive supervision should leave employees more likely to withdraw than to engage themselves heavily in their work'.…”
Section: Theoretical Implicationssupporting
confidence: 67%
“…Participants completed a 15-item measure developed by Tepper (2000) to disclose their perceptions of their leaders' abusive supervision behavior. Previous research reported acceptable alpha coefficients for the measure ranging from 0.83 to 0.97 (Chen and Wang, 2017; Huang et al , 2018; Mawritz et al , 2012). A sample item is: “My supervisor ridicules me.” In this study, the alpha coefficient was 0.96.…”
Section: Methodsmentioning
confidence: 92%
“…Barnes et al (2015) further suggested that researchers examine abusive supervision by exploring fluctuations in a given leader's abusive behaviors on a given day (Petrou et al , 2012). Therefore, considering a daily (day-to-day; Barnes et al , 2015; Huang et al , 2018) research design is insightful when investigating abusive supervision alongside cross-sectional and temporal designs. The third limitation is the nested data.…”
Section: Discussionmentioning
confidence: 99%
“…As a typical negative leadership behavior, abusive supervision has garnered increasing research attention due to its prevalence and resulting high costs (Huang et al., 2019; Mackey et al., 2015). Numerous studies have demonstrated that subordinates’ perceptions of abusive supervision are positively associated with counterproductive work behavior, workplace deviance, work‐to‐family conflict, and emotional exhaustion and are negatively associated with organizational citizenship behavior, performance, job satisfaction, and organizational commitment (e.g.…”
Section: Introductionmentioning
confidence: 99%